Roughness‐Based Method for Simulating Hydraulic Consequences of Both Woody Debris Clogging and Breakage at Bridges in Basin‐Scale Flood Modeling. Issue 12 (16th December 2021) - Macchione, Francesco; Lombardo, Margherita
Abstract: Obstructions at bridge can exacerbate flood hazard: when woody debris occlude a bridge, backwater increases, and sometimes a temporary reservoir can form. If the condition for the collapse of the jam exists, the phenomenon can evolve into a dam break flow resulting in an increase in downstream discharge or a steepening in the flow hydrograph. A rigorous description of backwater formed by debris at the bridge, and more generally of the interaction between flood and structure, is still a challenge and only few studies focus on the breakage phase and its consequence on flood dynamic. Unfortunately, analyzing the hydraulics of so many localized situations within a large area in detail would involve considerable modeling and calculation costs. Therefore, treatment methods are desirable that provide correct results in terms of the reference hydraulic variables for assessing the hazard without the need to model extremely local phenomena. The purpose of this study is to evaluate the possibility to reproduce an observed or estimated backwater by the use of an equivalent roughness at the place of the bridge and simulate the breakage phase by a sudden variation of its value. The method, applied to the numerical reconstruction of the experimental tests of dam break performed by the Waterways Experiment Station in 1961, has provided results that overlap well with the experimental values. Furthermore, it was applied to the reconstruction of the historical flood occurred in the Soverato river (Calabria, Italy). It did not require local grid refinement and provided results faithful to flood marks. Key Points: An easy‐to‐apply method for simulating hydraulic effects due to clogging and breakage at bridges has been set up and validated The method was applied for the numerical reconstruction of flood at basin‐scale in presence of clogging and breakage at bridges The inclusion of clogging and breakage simulation at bridges allowed for better agreement with flood marks and witness reports